Effect Of Brackish Water on the Growth and Yield of Hydroponically Grown Cherry Tomato: Hydroponically grown cherry tomato with brackish water - Doomra, Aarish; Choudhary, O.P.; R Sharda; MS Mavi (Journal of Soil Salinity and Water Quality, 2023)
Long-term use of saline water for irrigation deteriorates soil health. Therefore, instead of direct use of saline water for irrigation, there is a need to find the alternatives for using saline water rationally to sustain crop productivity and soil health. Growing vegetables in the nutrient film technique (NFT) in green house/poly house can be a good option to efficiently use the saline water. In this technology, hoagland solution is used to provide nutrition to the plants. A study was conducted to examine the  use of different grades of saline water in the green house using nutrient film technique of for cherry tomato production. Cherry tomato was grown in the five brackish water treatments including best available water (BAW, electrical conductivity (EC) 1.5 dS m-1) ,  and saline waters having 3.0, 4.5, 6.0 and 7.5 dS m-1 EC at demonstration farm of Department of Soil Water and Engineering, PAU, Ludhiana. Growth parameters (plant height, number of leaves and leaf area index) and fruit parameters (yield, number of fruits and fruit weight) were measured during the study. The cherry tomato plants irrigated with nutrient solution having EC of 3.0 dS m-1 was found the most suitable and effective to support plant growth parameters viz. plant height, number of leaves and leaf area index and achieved higher yield (1231 g plant-1), higher number of fruits per plant (117) and maximum fruit weight (10.5 g).It can be concluded that brackish water of 3.0 dS m-1 is viable option for raising cherry tomato when grown under NFT condition.